Cardiovascular complications of nasal packing after septoplasty. A randomized clinical trial // Complicaciones cardiovasculares del empaque nasal después de una septoplastia. Un ensayo clínico aleatorio - Taheri, Abolfazl; Moshkani Farahani, Maryam; Saeedi, Masoumeh; Banaei-Boroujeni, Shahin; Morteza Hosseini, Seyed (Investigación Clínica, 2020)
AbstractA common method employed in nasal surgery is the anterior nasal packing. One of the complications debated today is about the cardiovascular effects due to the use of this method. The purpose of this study was to evaluate some cardiac parameters in different groups of patients subjected to septoplasty, to identify the safest way to use nasal packing in postoperative treatment and to minimize its cardiovascular complications. In this clinical trial, 104 candidates for septoplasty were initially screened, of which, 14 patients were excluded and 90 patients were selected by block randomization. Different assessors monitored blood pressure, heart rate and cardiac rhythm three times before surgery. Then a classic septoplasty was performed in all patients, after which patients were randomly divided into three groups: 1) without nasal packing, 2) with nasal packing, and 3) with nasal packing that had an airway. Blood pressure and heart rate were monitored, following surgery, by a 24-hour Holter. The monitoring data were analyzed and interpreted by a cardiologist. The significance criteria of data were assumed as p-values ≤ 0.05. Mean diastolic blood pressures after surgery in groups 1-3 was: 73.4±7.3 mmHg, 76.4±5.8 mmHg and, 80.9±6 mmHg, respectively, showing lower values in patients without nasal packing and a significant difference in patients that had nasal packing with an airway (p=0.03). Mean heart rates after surgery in groups 1-3 were 71.8±11.3, 77.7±7.9 and 79.1±6.7, respectively, showing a significant difference of the first group with respect to group 3 (p=0.043). This research showed that the use of anterior nasal packing with or without airway leads to cardiovascular changes such as increased diastolic blood pressure and heart rate. More studies should be conducted for a definitive conclusion, so the balance of its risks and benefits must be considered, when using nasal packing after septoplasty surgery.ResumenEl empaque nasal es un método común utilizado en la cirugía de la nariz. Una de las complicaciones que se discuten en la actualidad son las posibles complicaciones cardiovasculares producidas por este método. El propósito de este estudio fue evaluar algunos parámetros cardíacos en diferentes grupos de pacientes sometidos a septoplastia, la manera más segura de utilizar el empaque nasal en el tratamiento postoperatorio y minimizar sus complicaciones cardíacas. En este ensayo clínico se examinaron, inicialmente, 104 candidatos a septoplastia, de los cuales se excluyeron 14 y se seleccionaros 90 pacientes, divididos en bloques de forma aleatoria. Diferentes asesores evaluaron la presión arterial, la frecuencia y el ritmo cardíacos en tres oportunidades, antes de la cirugía. Posteriormente se realizó una septoplastia a todos los pacientes seleccionados y se dividieron en tres grupos al azar: 1) sin empaque nasal, 2) con empaque nasal y 3) con empaque nasal y vía aérea. La presión arterial y la frecuencia cardíaca fueron monitoreadas durante 24 horas después de la cirugía, mediante un Holter. Los datos obtenidos mediante este método fueron analizados e interpretados por un cardiólogo. El criterio de significancia para estos datos se asumió como p≤ 0.05. Las presiones arteriales diastólicas medias en los grupos 1-3 fueron: 73.4±7.3 mmHg, 76.4±5.8 mmHg y 80.9±6 mmHg, respectivamente, ocurriendo los valores más bajos en pacientes sin empaque nasal y con una diferencia significativa en pacientes con empaque nasal con vía aérea (p=0.03). Las frecuencias cardíacas media después de la cirugía en los grupos 1-3 fueron: 71.8±11.3, 77.7±7.9 and 79.1±6.7, respectivamente; existiendo una diferencia significativa entre el primer grupo y el grupo 3 (p=0.043). Este estudio demostró que el uso de empaque nasal anterior, con o sin vía aérea, conduce a cambios cardiovasculares, tales como aumento de la presión arterial diastólica y la frecuencia cardíaca. Se deben realizar estudios adicionales para llegar a una conclusión definitiva y se deben considerar los riesgos y beneficios de utilizar el empaque nasal después de una septoplastia.